Biodegradable plastic film mulch increased nitrous oxide emissions in organic leek but decreased emissions in organic cabbages - Samphire, Martin; Jones, Davey L.; Chadwick, David R. (Frontiers in Agronomy, 2025)
Plastic film mulch (PFM) controls weeds and increases yields, making it attractive to vegetable growers; biodegradable PFMs potentially reduce the harms associated with conventional PFMs. PFMs increase soil biological activity, accelerating the decomposition of soil organic matter and potentially increasing emissions of some greenhouse gases (GHGs). Conversely, they are a barrier to rainfall infiltration and gas exchange, reducing harmful nitrate (NO3-) leaching and ammonia (NH3) volatilisation. The effects of PFMs on the processes resulting in GHG emissions are not well explored outside conventionally grown commodity crops in major growing regions. To address this, we conducted a field experiment on an organic vegetable farm with a temperate maritime climate. We measured nitrous oxide (N2O), methane (CH4), carbon dioxide (CO2) and potential NH3 emission from the soil, growing leeks or cabbages, with or without biodegradable PFM and amended with poultry manure or green-waste compost. Averaged across both crops, yield was 26% higher with PFM; potential NH3 emissions were 18% lower (43% on a yield-scaled basis) in mulched treatments than unmulched; CH4 emissions were not significantly affected. Yield-scaled N2O emissions were 62% higher in mulched leeks than unmulched but 56% lower in mulched cabbages than unmulched; this coincided with higher soil NO3- content in mulched leeks than either unmulched crop or mulched cabbages. Results were not obtained for CO2, so partial global warming potential (GWP) and greenhouse gas intensity (GHGI) were determined mainly by N2O emissions. Overall, our results indicate that biodegradable PFM can potentially reduce harmful gaseous N emissions in organic horticulture.